Volume variation may be a relevant metric in the study of aneurysm pulsatility: a study using ECG-gated 4D-CTA (PULSAN). (7th November 2019) - Dissaux, Brieg; Ognard, Julien; Cheddad El Aouni, Mourad; Nonent, Michel; Haioun, Karim; Magro, Elsa; Gentric, Jean Christophe
Abstract : ​Background and purpose: Intracranial aneurysms are a frequently occurring disease, with an estimated prevalence of 2–5% in the general population. They usually remain silent until rupture occurs, with a mortality rate of 35–50% and a high rate of morbidity, including long-term disability. However, preventative treatments have their own risk of complications and morbi-mortality rates, including stroke and hemorrhage. ECG-gated four-dimensional CT angiography (4D-CTA) allows the acquisition of time-resolved three-dimensional reconstructions. The aim of our study was to evaluate different intracranial aneurysm metrics over the cardiac cycle using ECG-gated 4D-CTA. ​Materials and methods: ECG-gated 4D-CTA datasets were acquired in patients presenting with intracranial aneurysms. Seven aneurysm metrics, including aneurysm height, aneurysm length, ostium width, aspect ratio, ostium area, volume, and volume-to-ostium ratio, were analysed over different cardiac phases. Intra-reader agreement, inter-reader agreement, and inter-cycle agreement were calculated through the intraclass correlation coefficient. ​Results: Twenty-one aneurysms from 11 patients were considered for inclusion. Post-processing failed for three aneurysms, and 18 aneurysms were finally analysed. There was good intra-reader agreement for each metric (ICC >0.9). Agreements among three consecutive cardiac cycles were calculated for six aneurysms and were especially good for the volume metric (ICC >0.9). Volume variation appears to be the most relevant metric and seems especially perceptible for aneurysms larger than 5 mm. ​Conclusions: Quantification of aneurysm volume changes during the cardiac cycle seems quantitatively possible and reproducible, especially for aneurysms larger than 5 mm. Further studies need to be conducted to validate this parameter for intracranial aneurysm assessment.